Avaliação do Bevacizumabe como modulador em modelo experimental de cicatriz palpebral de coelhos - Paiva, Carolina Bonfim de (2020)
The objective of this study was to investigate the effects of bevacizumab, an inhibitor of the vascular endothelial growth factor activity, after intralesional administration in eyelid scars of rabbits. Identical bilateral linear wounds were created with a #15 scalpel blade in the periocular region of each rabbit. The wounds healed by second intention, and 1 month postoperatively, apparently similar scar formation was confirmed bilaterally on inspection. On postoperative day 30 (between the scar maturation phase and the beginning of the remodeling phase), all scars on the right side were administered with a subcutaneous injection of bevacizumab (2.5 mg/0.1 mL) in the middle third of the total scar extension. The left side (contralateral) was not treated, and it served as a control. One month later, the eyelid scars and general health of the rabbits were evaluated. After checking for intact and morphologically similar wounds through simple inspection, the animals were euthanized. Subsequently, the periocular scar material was collected by removing its entire length with a scalpel blade and sent for histological evaluation of the quantity of new vessels, collagen subtypes, and scar elevation index. This study included nine 5-month-old New Zealand rabbits weighing 4 to 4.5 kg. The mean scar elevation index score was 1.35 on the treated side and 1.80 on the untreated side (p = 0.001). Further, neovascularization was lesser (88,9% vs 22,2%) (p = 0.006) in the eyelids treated with bevacizumab compared to controls. In this animal model, the administration of bevacizumab was associated with a reduced rate of scar elevation and reduced neovascularization.